Pengaruh Kualitas Produk dan Citra Merek Terhadap Keputusan Pembelian Konsumen dalam Membeli Produk Kerupuk PT.Legong Bali Nusantara Pandaan - Sidoarjo - Fauzi, Agustina Rizky (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The expansion of business which is getting more dynamic, has propelled the enterprises to be more active in building stategy to preserve their products in market. One of the strategy which can be implemented by the enterprises is by giving the best quality in their products so the consumers have trust that the product they consumed has good quality. In addition, there’s one thing that must be noticed is the image brand owned by disrepute of the brand can influence the selling values which can be produced by the product so that so that’s the improtance to keep the brand image.Based on the purposes of the research which is set, so the kind of research is explanatory research to know and analyze the decision of the consumers in buying the crackers product of PT. Legong Bali Nusantara. The Sample of this research is 100 respondents whose the consumers of PT. Legong Bali Nusantara crackers with using purposive sampling techniques. In collecting data, the writer use questionnaire dissemination, library research, and broswing.Besed on the result of experiment by using the tools of experiment in research, which are validity test, reliabilty test, classic assumption test, and hypotheses test are implemented by using test F and test T, the next step data analysis used is double linier regression, the conclusion is product quality variable has positive effect and significant to consumer satisfaction in buying PT. Legong Bali Nusantara. Mean while brand image variable has less influence and less significant in consumers decision in buying crackers product of PT. Legong Bali Nusantara.Key : Qualty Product, Brand Image, and Buying Decision.